MORFOLOGI DAN KLASIFIKASI TANAH PADA TOPOSEKUEN LERENG BARAT GUNUNG KELUD, KEDIRI, JAWA TIMUR - Rizki Delfianto; Mochtar Lutfi Rayes; Christanti Agustina (Jurnal Tanah dan Sumberdaya Lahan, 2021)
The research that was conducted from April to December 2020 in the Supiturung Micro-Watershed, located on the western slope of Mount Kelud, Kediri was aimed to study the morphological characteristics and soil classification using a topo-sequence approach. Four pedons were observed across the physiographic positions (upper, middle and lower slopes) on dry-land farming land use. The method used in this research included 8 stages, namely the preparation stage, pre-survey, map making, field observations, laboratory analysis, soil classification, data processing, and reporting. On the field, cross-sectional profiles were carried out on four selected pedons by testing the soil profile measuring 1 x 1 meter with a depth of 150-200 cm, followed by soil horizon, soil thickness, texture, structure, consistency, effective depth, type and number of pores, as well as other characteristics. Soil samples were collected from the genetic horizon of the pedons for being analyzed using standard procedures, then taken to the laboratory for soil physical and chemical analysis. Soil morphology with physicochemical properties was then classified based on the Keys Taxonomy of Soil to the Sub Group level. The results showed that each pedon has a different Sub Group. This condition can be caused by many factors, such as differences in epipedon thickness, base saturation values, organic C levels, and other morphological conditions at the time of direct observation. Four pedons have lithologic discontinuities, recognition of these types of lithologic changes is important because pedogenesis and pedogenic interpretations are greatly influenced by changes in the parent material.